Challenges in Eye Care in the Asia-Pacific Region. Issue 5 (September 2021) - Yusufu, Mayinuer; Bukhari, Javaria; Yu, Xiaobin; Lin, Timothy P.H.; Lam, Dennis S.C.; Wang, Ningli
Abstract : N/A: The Asia-Pacific region is home to a 4.3-billion population and one of the most rapidly aging regions. Addressing the eye care needs in the region would greatly boost the progress toward achieving universal eye health. Over 20 countries/regions have actively engaged in the "VISION 2020" initiative launched since 1999, and remarkable achievements have been witnessed as demonstrated by an increase in both the number and density of ophthalmologists in almost all countries. Nevertheless, formidable and emerging challenges are to be overcome in the coming century. From 1990 to 2015, the absolute number of blind people increased by 17.9%, largely due to population growth and aging. The Asia-Pacific region, the most populous continent with a rapidly aging population, would inevitably be left to tackle this challenge. Furthermore, a high prevalence of blinding eye diseases imposes great pressure on current eye care services, with South Asia having the highest age-standardized prevalence of moderate to severe visual impairment (17.5%) and mild vision impairment (12.2%) globally, and high-income countries having the highest overall prevalence of myopia, reaching 53.4% with East Asia having the second-highest overall prevalence (51.6%). Moreover, the availability of ophthalmic resources varies greatly in the region, with the density of ophthalmologists ranging from over 114 ophthalmologists per million population in Japan to 0 in Micronesia, and a highly disproportionate urban-rural distribution. This article aims to shed light on challenges faced by the Asia-Pacific ophthalmic community and propose corresponding strategies to tackle those challenges. Abstract : Supplemental Digital Content is available in the text